Fertilizer best management practices by SSNM and customized fertilizers for elephant foot yam (Amorphophallus paeoniifolius) cultivation in India - BYJU, G; NEDUNCHEZHIYAN, M; GEORGE, JAMES; SUNITHA, S; KAMALKUMARAN, R; SINGH, P P; MAMATHA, K; MITRA, SURAJIT; TARAFDAR, JAYANTA; DESAI, KETAN; RAVI, V; VANI, M; et al. (The Indian Journal of Agricultural Sciences, 2016)
Elephant foot yam [Amorphophallus paeoniifolius (Dennst.) Nicolson] is an important tuber crop grown in many parts of India for its starchy corm and the average yield of this crop is far below the potential productivity of 100 tonnes/ha. One of the reasons attributed to the lower yield is the imbalanced application of essential plant nutrients. Site specific nutrient management (SSNM) is the application of plant nutrients based on the soil and crop need, yield target and developed with the aid of models such as QUEFTS. This paper gives the result of four year study conducted to calibrate and validate the QUEFTS model for elephant foot yam cultivation and the development of SSNM zonation maps and secondary and micronutrient fortified customised fertilizers for the crop in major growing environments of India. Data collected from different field experiments conducted in major elephant foot yam-production regions of India during 1968 to 2011 were used to calibrate the model. The derived parameters of minimum and maximum accumulation of N (130 and 460), P (900 and 2100) and K (100 and 170) are proposed as standard borderline values in the QUEFTS model for elephant foot yam. A linear increase in corm yield was suggested by the model with N, P and K uptakes of 3.97, 0.71, and 7.05 kg N, P and K/1 000 kg corm. The average NPK ratio in total plant dry matter was 5.56:1:9.88. Based on these results, the model was calibrated using historical data as well as by conducting field experiments. It can be observed that fertilizer best management practices by SSNM resulted in an average actual corm yield of 33.45 tonnes/ha, whereas, the model predicted a yield of 35 tonnes/ha. The results of the study showed good agreement between predicted and measured corm yields during the four years, which indicated that the calibrated model can be used to improve NPK fertilizer recommendations for elephant foot yam in India. Based on the results and using soil fertility maps and agro ecological unit maps, SSNM zonation maps and secondary and micronutrient fortified customised fertilizers were developed for major elephant foot yam growing environments of India.